Impacto do aproveitamento de água da chuva na drenagem: estudo de caso de um condomínio horizontal em Curitiba/PR - Teston, Andrea (2015)
The false idea that water is an unlimited natural resource is supported by the water cycle, and therefore the issue has been neglected for too long. Nowadays, however, the water problem on the planet has exceeded the boundaries of countries suffering from shortages. It results in a constant search for programs of water conservation and use of alternative sources for human consumption, including the use of rainwater. This paper presents, as the main objective, the verification of the impact of rainwater harvesting system in single family residences at consumption of drinking water and urban drainage. Through the case study of a horizontal condominium in the city of Curitiba, Paraná, it presents a quantitative assessment of the volume of rain that is used and overflowed, using two methods of sizing tank volume: Method Practical German (ABNT 15,527 / 2007) and Method of Decree 293/2006 of Curitiba. Furthermore, it uses daily rainfall data since 1997 until 2013 to creates three demand scenarios of rainwater. With it is possible to verify the efficiency and confidence of the adopted systems in order to determine how much of the demand is met and how much water is retained in reservoirs.